Sub-cycle valleytronics: control of valley polarization using few-cycle linearly polarized pulses - Jimenez-Galan, Alvaro; Silva, Rui E. F.; Smirnova, Olga; Ivanov, Misha (Optica, 2021)
So far, it has been assumed that selective excitation of a desired valley in the Brillouin zone of a hexagonal two-dimensional material has to rely on using circularly polarized fields. We theoretically demonstrate a way to control the valley excitation in hexagonal 2D materials on a few-femtosecond timescale using a few-cycle, linearly polarized pulse with controlled carrier–envelope phase. The valley polarization is mapped onto the strength of the perpendicular harmonic signal of a weak, linearly polarized pulse, which allows to read this information all-optically without destroying the valley state and without relying on the Berry curvature, making our approach potentially applicable to inversion-symmetric materials. We show applicability of this method to hexagonal boron nitride and MoS2.
CRIS-Team Scopus Importer:2023-04-20